The Problems of Social and Information Support of the Population of the Arctic Zone of Russia in the Cut of the Industrialization of the Development of the Region. / Los problemas del apoyo social y de información a la población de la zona ártica de Rusia en la reducción de la industrialización del desarrollo de la región - Belonozhko, Marina L.; Barbakov, Oleg M.; Belonozhko, Lidiya N. (Utopía y Praxis Latinoamericana)
ABSTRACT Interest in the Arctic zone was determined mainly due to the political and economic situation, the use of its rich resource potential, national security, and increased international political influence. But, in the studied region there are social problems that were investigated by the authors. It has been established that the strength side of the Arctic region is its qualitative composition of the population. The weak side is poor development of the social environment. But in the region there are opportunities for its development, which consist in the creation of new jobs. The author suggests that more attention should be paid to medicine, education, environmental aspects. RESUMEN El interés en la zona Ártica se ha determinado principalmente por la situación política y económica, el uso de su rica capacidad de recursos, la seguridad nacional, el fortalecimiento de la influencia política internacional. Pero, en la región investigada también hay problemas sociales que han sido investigados por los autores. Se ha determinado que la composición cualitativa de la población es el punto fuerte de la región del Ártico. Desarrollo social débil. Pero en la región hay oportunidades para su desarrollo, que son la creación de nuevos puestos de trabajo. Los autores sugieren que se debe prestar más atención a la medicina, la educación y los aspectos ambientales